2020
DOI: 10.1016/j.isci.2020.101361
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Human Olfactory Perception from Activities of Odorant Receptors

Abstract: Machine learning predicted activity of 34 human ORs for~0.5 million chemicals Activities of human ORs could predict odor character using machine learning Few OR activities were needed to optimize predictions of each odor percept Behavior predictions in Drosophila also need few olfactory receptor activities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…The essential CmaxORs and relevant key amino acid residues provided in this work can be prioritized in future functional demonstrations. Because more promising results were achieved using in silico approaches, we may save a lot of time finding precise insect regulators in the future 58 . The concept of reverse chemical ecology can be expanded by adding in silico methods in the future, and experiments can be designed more specifically to evaluate the functions of certain amino acid residues 59,60 .…”
Section: Discussionmentioning
confidence: 99%
“…The essential CmaxORs and relevant key amino acid residues provided in this work can be prioritized in future functional demonstrations. Because more promising results were achieved using in silico approaches, we may save a lot of time finding precise insect regulators in the future 58 . The concept of reverse chemical ecology can be expanded by adding in silico methods in the future, and experiments can be designed more specifically to evaluate the functions of certain amino acid residues 59,60 .…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve upon and further validate the analysis, experimental methods involving a standardised chemotaxis assay can be employed for a set of chemicals, and numerical chemotactic index values can be calculated and fed into machine learning models in place of the current categorical binaries. It has been shown that the incorporation of odorant receptor data increases the accuracy of prediction in humans [76]. However, there is only a limited set of olfactory receptor data available for C. elegans due to the complexity arising from their co-expression on neurons and the presence of a large number(≈1200) of GPCR genes [30, 77].…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning algorithms for feature selection are from the caret [32] and kernlab [33] packages in the R programming language and similar to the way it has been used for ligand prediction of human odorant neurons [34].…”
Section: Selecting Important Chemical Featuresmentioning
confidence: 99%